Ath-Thulab Al-Qulqun li Ta'allum Al-Lughat Al-Ajnabiyah fi Indonesia - M. Imam Fakhrurrozy; M. Kholis Amrullah; Manna Dey (Institut Agama Islam Negeri (IAIN) Metro, 2023)
Teachers very rarely notice students' language anxiety. One of the implications of anxiety is that students are passive when learning languages, especially learning related to speech skills; most teachers perceive it as demotivated, lack of interest, and cognitive failure. The research was conducted by interviewing teachers and learners at UIN Antasari and IAIN Metro. Meanwhile, in-depth interviews are conducted to dig up information. The results showed several findings, such as the source of anxiety dominated by language errors raised by learners. The results of a search of teachers prove that the source of language anxiety is the ability to speak. The results of the theoretical discussion showed that the positive side of language anxiety is that it encourages learners to increase learning activities in the classroom.